Ensaio sobre a democracia socialista: um modelo para o Brasil contemporâneo - Menezes Neto, Gilberto Moreira (2025)
Democracy in Brazil is going through turbulent times. Institutions have their autonomy questioned, while the Welfare State strengthened by the enactment of the 1988 Constitution is gradually being dismantled. However, this process does not seem to be exclusive to Brazil, given that countries historically seen as consolidated democracies are now witnessing the rise of an anti-democratic far right, after decades of neoliberal policies. Meanwhile, the opposition to these groups here in Brazil, known as the “left,” is finding it difficult to reestablish a coalition government between different socioeconomic classes, due to the fact that the increase in economic inequality between classes in recent decades has translated into an increase in political inequality. Therefore, based on bibliographical research, this essay develops an analysis of this contemporary democratic crisis and of socialism from the perspective of the challenges of the 21st century. For practical purposes, this essay develops a proposal for a set of public policies that attempt to mitigate this crisis experienced by Brazilian democracy established by the 1988 Constitution based on socialist strategies. Thus, this model of public policies is called Socialist Democracy.